Tsunami vs storm origin for shell bed deposits in a lagoon enviroment: an example from the Upper Cretaceous of Southern Patagonia, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The criteria by which the deposits of tsunamis are distiguished from other deposits, including storm surges, have been controversial for more than 10 years. The Mata Amarilla Formation of the lower Upper Cretaceous of Southern Patagonia has excellent outcrops that in its lower section, sedimentary and taphonomic characteristics suggest a tsunami origin. This paper presents details of these aspects, as well as a model of temporal stages that led to their deposition within a lagoon. The sediments are composed of alternating white sandstones and mudstones, with interbedded bioclastic accumulations in the lower section. The depositional environment was characterised by a lagoon bounded by shallow marine bars. These fine-grained sediments are sporadically interrupted by tsunami events represented by coquinas, bioclastic sands and shell pavements with allochthonous and autochthonous mollusk associations from freshwater and marine habitats. Some areas of the lagoon became exposed, thus enabling the development of vegetation on the substrate and pedogenic processes. Subsequently, a forced regression occurred when a fluvial system invaded the lagoon area, representing the beginning of the deposition of the middle section of the Mata Amarilla Formation.